Functional Consequence of Positive Selection Revealed through Rational Mutagenesis of Human Myeloperoxidase - Loughran, Noeleen B. (Oxford University Press, 2012)
Myeloperoxidase (MPO) is a member of the mammalian heme peroxidase (MHP) multigene family. Whereas all MHPs oxidize specific halides to generate the corresponding hypohalous acid, MPO is unique in its capacity to oxidize chloride at physiologic pH to produce hypochlorous acid (HOCl), a potent microbicide that contributes to neutrophil-mediated host defense against infection. We have previously resolved the evolutionary relationships in this functionally diverse multigene family and predicted in silico that positive Darwinian selection played a major role in the observed functional diversities (Loughran NB, O'Connor B, O'Fagain C, O'Connell MJ. 2008. The phylogeny of the mammalian heme peroxidases and the evolution of their diverse functions. BMC Evol Biol. 8:101). In this work, we have replaced positively selected residues asparagine 496 (N496), tyrosine 500 (Y500), and leucine 504 (L504) with the amino acids present in the ancestral MHP and have examined the effects on the structure, biosynthesis, and activity of MPO. Analysis in silico predicted that N496F, Y500F, or L504T would perturb hydrogen bonding in the heme pocket of MPO and thus disrupt the structural integrity of the enzyme. Biosynthesis of the mutants stably expressed in human embryonic kidney 293 cells yielded apoproMPO, the heme-free, enzymatically inactive precursor of MPO, that failed to undergo normal maturation or proteolytic processing. As a consequence of the maturational arrest at the apoproMPO stage of development, cells expressing MPO with mutations N496F, Y500F, L504T, individually or in combination, lacked normal peroxidase or chlorinating activity. Taken together, our data provide further support for the in silico predictions of positive selection and highlight the correlation between positive selection and functional divergence. Our data demonstrate that directly probing the functional importance of positive selection can provide important insights into understanding protein evolution.